КАЗАХСТАН И ИНДИЯ: РАСШИРЯЮЩИЕСЯ ГОРИЗОНТЫ ДВУСТОРОННЕГО СОТРУДНИЧЕСТВА - Nurdavletova L.M.; Movkebayeva G.А. (Известия. Серия: Международные отношения и регионоведение, 2025)
This paper examines the comprehensive development of bilateral relations between the Republic of Kazakhstan and the Republic of India, tracing their evolution from the establishment of diplomatic ties in 1992 to the present-day strategic partnership. Over the past three decades, Kazakhstan and India have demonstrated a consistent commitment to expanding cooperation across a wide array of sectors, including politics, trade and investment, energy, education, culture, defense, and emerging technologies. The paper provides an in-depth analysis of the key phases of diplomatic engagement, marked by frequent high-level visits, the signing of crucial agreements, and the institutionalization of mechanisms for political dialogue and economic cooperation. Special attention is given to the role of both countries within multilateral platforms such as the United Nations, the Shanghai Cooperation Organization (SCO), and the Conference on Interaction and Confidence-Building Measures in Asia (CICA). Their shared positions on global challenges – including counterterrorism, nuclear non-proliferation, regional stability, and sustainable development – reflect a growing convergence of strategic interests. Furthermore, the paper explores the significance of new areas of cooperation, including green energy, digitalization, space technology, and transport logistics, emphasizing the shift from traditional diplomatic interaction to multidimensional partnership. The resilience of Kazakhstan-India relations during global crises, such as the COVID-19 pandemic, demonstrates the strength and flexibility of their bilateral ties. Ultimately, the research concludes that Kazakhstan and India have successfully built a dynamic and future-oriented relationship grounded in mutual respect, shared values, and common goals. Their continued collaboration promises to play an increasingly influential role in shaping regional geopolitics and fostering stability, prosperity, and connectivity across Central and South Asia.